2008
DOI: 10.1002/pon.1420
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of affect following treatment decision‐making for prostate cancer: conversations, cognitive processing, and coping

Abstract: Greater time spent talking with family and friends about treatment options may provide opportunities for patients to cope with their cancer diagnosis and facilitate cognitive processing, which may improve patient distress over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…Although research suggests that both problem-focused coping and meaning-focused coping are helpful (e.g., Christie, Meyerowitz, Giedzinska-Simons, Gross, & Agus, 2008, Tomaka, Blascovitch, Kelsey, & Leitten, 1993, and are mediators of the appraisal-adjustment link, very little research has directly pitted the effects of these two types of coping in the same study within the context of appraisals and adjustment. Additionally, no studies to our knowledge have compared the helpfulness of problem-focused and meaningfocused coping as mediators between appraisal and adjustment within the context of ongoing stressors.…”
Section: The Current Study: Problem-focused Vs Meaning-focused Copingmentioning
confidence: 96%
“…Although research suggests that both problem-focused coping and meaning-focused coping are helpful (e.g., Christie, Meyerowitz, Giedzinska-Simons, Gross, & Agus, 2008, Tomaka, Blascovitch, Kelsey, & Leitten, 1993, and are mediators of the appraisal-adjustment link, very little research has directly pitted the effects of these two types of coping in the same study within the context of appraisals and adjustment. Additionally, no studies to our knowledge have compared the helpfulness of problem-focused and meaningfocused coping as mediators between appraisal and adjustment within the context of ongoing stressors.…”
Section: The Current Study: Problem-focused Vs Meaning-focused Copingmentioning
confidence: 96%
“…11 Advice from others also has been linked to patients' perceptions of greater social support and increased emotional expression after decision-making. 41 Messages and communication that provide tangible assistance and reassurance and medical information in a language that patients understand were associated with the patient's treatment decision and decision-making process. 42 It is possible that patients who have received more treatment-related advice from others believe that their treatment decision has been influenced more by others, especially by their physician(s), but less by themselves than what actually has happened.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these data strongly suggest that AAT side effects are a potential pathway between AAT and clinical levels of anxiety (the presence of a similar link with depression requires replication with a larger sample, although the size of the correlation suggests that such a link exists). If, as has been demonstrated previously, elevated anxiety and depression contribute to impaired decision making and place limitations on treatment efficacy with PCa patients (Christie et al, 2009;Thomas et al, 2009), then AAT side effects may be an instigator factor in that process.…”
Section: Discussionmentioning
confidence: 92%
“…There is also evidence that elevated anxiety and depression in this patient group can have powerful and extended effects during the treatment phase by interfering with decision making (Christie, Meyerowitz, Giedzinska-Simons, Gross, & Agus, 2009), perhaps reducing the longer term success of treatment and further limiting patients' chances of recovery (Thomas, Thomas, Nandamohan, Nair, & Pandey, 2009). These data are in accord with those from a major metaanalysis based upon 25 studies of patients experiencing a range of illnesses (e.g., cancer, angina, end-stage renal disease, and arthritis), which showed that anxious and depressed patients are 3 times more likely to be noncompliant with their medication regime than nonanxious or nondepressed patients (DiMatteo, Lepper, & Croghan, 2000).…”
mentioning
confidence: 97%